Detection of Shunting Into Pulmonary Artery on Multidetector Row Computed Tomography Arteriography Before Bronchial Arterial Embolization: A Preliminary Study. Issue 6 (November 2020) - Takeuchi, Hitoshi; Matsumoto, Tomohiro; Morimoto, Kozo; Osawa, Takeshi; Tanaka, Yoshiaki; Yoshimori, Kozo; Kamei, Shunsuke; Yamamoto, Shota; Kurosaki, Atsuko; Hasebe, Terumitsu
Abstract : Objective: The aim of this study was to investigate the diagnostic performance of detecting systemic arterial pulmonary circulation shunts on multidetector row computed tomography arteriography (MDCTA). Methods: Thirty-five consecutive bronchial artery embolization sessions with preprocedural MDCTA were performed for 32 patients and 35 sessions. The MDCTA studies with computed tomography value of pulmonary trunk visually lower than that of ascending aorta were defined as "diagnostic MDCTA." Angiographic studies and "diagnostic MDCTA" were evaluated, respectively, for shunting into pulmonary artery. Based on the results of angiographic studies, diagnostic performance of "diagnostic MDCTA" was evaluated. Results: The rate of diagnostic MDCTA was 63% (23 of 35). On "diagnostic MDCTA, " sensitivity, specificity, and positive and negative predictive values for detecting shunts were 83% 100%, 100%, 94%, respectively. Conclusions: Systemic arterial pulmonary circulation shunts were detected on "diagnostic MDCTA" with high sensitivity and specificity.